(untitled) (Altre Modernità, 2024)
The paper aims to explore through discourse lens the rise of a new feminist imaginary, rooted in the Global South, with a specific focus on Latin American countries. More precisely, an attempt will be made to delve into the specificity that has led Latin America to create a new feminist and transfeminist geography grounded in the intersectional perspective, the upheaval of the colonial order, as well as issues related to labour, gender, race and class (Gago et al., 8M). A particular reference will be made to the Latin American discursive imaginary that identifies gender-based violence and the depredation of the territories as two sides of the same coin. This discursive frame can be encapsulated in the image of the body-territory, to be defended through alternative models of community care (Federici, piel). The work of scholars such as Silvia Rivera-Cusicanqui, Rita Segato, and others will be explored to understand how contemporary Latin American feminist thought, highlighting the global imperative to reconsider bodies and territories as sites of both productive and reproductive exploitation, is influencing activism and mobilization against the Anthropocene crisis.